(untitled) (Journal of The Colloquium for Information Systems Security Education, 2018)
Quantum cryptography and key exchange is an important and challenging topic for cybersecurity and information assurance students, and one that is difficult to teach without an appropriate demonstration platform. In this paper, we describe the background of quantum key exchange (QKE) theory, modern implementations of QKE, and the role it plays in classical, symmetric key cryptography. We present a QKE simulator that can be used by educators to aid in the teaching of quantum key exchange concepts and processes. The simulator provides a hands-on learning mechanism with which the participants interact. It is designed to be engaging and practical for students to use by supporting the ability to walk through phases of quantum key exchange, pausing at each step, to facilitate discussion and comprehension of this complex security topic.